PENGARUH JUMLAH KUNJUNGAN WISATAWAN, TINGKAT HUNIAN HOTEL, LAMA TINGGAL WISATAWAN TERHADAP PAD KABUPATEN/KOTA PROVINSI BALI - Widyasning, I Gusti Ayu Putu Sasih; Bendesa, I Komang Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
The purpose of this study was to determine how the influence of the number of tourist visits, hotel occupancy rates, and length of stay of tourists on Regency/City Original Regional Revenue (PAD) in Bali Province. This study uses an associative quantitative approach. The number of observations in this study amounted to 72. The data used is secondary data using panel regression data analysis technique. The results of simultaneous test, the number of tourist visits, hotel occupancy rates and length of stay had a simultaneous effect on PAD in Regencies/Cities in Bali Province in 2013-2020. Partially, the number of tourist visits had a significant positive effect on Regency/City PAD in the Province of Bali in 2013-2020. Hotel occupancy rates have no significant effect on Regency/City PAD in Bali Province in 2013-2020. The length of stay of tourists has no significant effect on Regency/City PAD in the Province of Bali in 2013-2020.